(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Smart contracts are self-executing agreements deployed on blockchain platforms. Their correct development and the choice of underlying algorithms play a crucial role in ensuring trust, efficiency, and security in decentralized systems. This thesis explores different methods for creating smart contracts and analyzes the algorithms used in various stages, such as consensus mechanisms, cryptographic functions, and execution models. Comparative analysis is performed on the basis of performance, scalability, and vulnerability resistance. The study provides insights for developers and researchers working on secure and efficient smart contract systems.